Linking Ecosystem Services to Social Well-Being: An Approach to Assess Land Degradation - Sharafatmandrad, Mohsen; Khosravi Mashizi, Azam (Frontiers in Ecology and Evolution, 2021)
Land degradation usually leads to the loss of ecosystems services which may threaten the social well-being. There is no approach to identify and manage all ecosystem services based on their importance in degradation process and social systems. This study aimed to link ecosystem services to social well-being in order to assess rangeland degradation. Eleven ecosystem services (forage production, water yield, edible plants, fuel, medicinal plants, pollination, gas regulation, soil resistivity to erosion, soil fertility, scene beauty, recreation) were assessed in a semi-arid rangeland near Bardsir city, Kerman province, southeast Iran. There was a significant differences between rangeland types in providing ecosystem services (p<0.05). Four criteria and 17 indices of social well-being were weighed according to their importance for local stakeholders. Rangeland degradation was estimated using the weight of indices for the social well-being and ecosystem services. Discriminant analysis indicated that supporting services (soil fertility) and provisioning services (water yield, forage production) had the greatest impact on the rangeland degradation, which is related to food security in social well-being. Ecosystem services and social well-being declined in medium and severe degradation due to plant composition change and overgrazing based on PCA. More than 70% of the watershed has been highly and severely degraded. There was a trade-off relationship between ecosystem services and social well-being in very severe degraded areas because of social well-being promotion due to agriculture expansion. Based on our approach, the loss rate ecosystem services and social well-being indices in each degradation category is a good guide for management programs and decision-makers to meet both the needs of the people and the preservation of ecosystems.